2010
DOI: 10.3892/etm.2010.142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of evaluations of hormone receptors in breast carcinoma by image-analysis using three automated immunohistochemical stainings

Abstract: Abstract. the aim of this study was to compare the results of immunohistochemistry (ihc) assays evaluated by human examiners with the results evaluated by computerized image analysis, and to compare the computerized image analysis results among three automated ihc assays, namely the BioGenex, dako and Ventana assays. all slides were semiquantitatively evaluated according to the allred score and J-score by human examiners. the images were analyzed using macScOpE version 2.6 for macintosh according to the h-scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Currently there is no consensus cutoff for H‐score for the AR immunohistochemistry. One study evaluated the cutoff value of H‐score using the DAKO, Ventana, and BioGenex assays for hormone receptors and found the optimal cut‐off values of H‐score were 36, 24, and 34, respectively . In this study, an H‐score ≥40 defined a positive AR expression; and an H‐score <40 defined negative AR expression.…”
Section: Methodsmentioning
confidence: 86%
“…Currently there is no consensus cutoff for H‐score for the AR immunohistochemistry. One study evaluated the cutoff value of H‐score using the DAKO, Ventana, and BioGenex assays for hormone receptors and found the optimal cut‐off values of H‐score were 36, 24, and 34, respectively . In this study, an H‐score ≥40 defined a positive AR expression; and an H‐score <40 defined negative AR expression.…”
Section: Methodsmentioning
confidence: 86%
“…The equation was based on the scoring system developed and used by Allred et al for the evaluation of oestrogen and progesterone receptor expression in breast carcinoma (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…Because the current cut point for hormone receptor positivity is very low (> 1% cells), minor differences in antibody sensitivity may alter hormone receptor status [47]. Comparing two manual and three automated systems, investigators concluded that the concordance rates were excellent among the three most commonly used antibodies, clone 6F11, 1D5, and 5p11 [48]. However, other investigators found that the 1D5 antibody is less sensitive than other antibodies, including SF11 [49].…”
Section: Specimen Analysis 221 Technical Factorsmentioning
confidence: 99%